Principio europeo di non discriminazione religiosa e approcci nazionali alla “neutralità” del pubblico dipendente (Stato, Chiese e pluralismo confessionale, 2023)
Principle of non-discrimination on the grounds of religion in EU law and national approaches to the "neutrality" of the public employeeABSTRACT: For the first time, the Court of Justice of the European Union has been called upon to give a preliminary ruling on prohibition on wearing visible signs of political, philosophical or religious belief imposed by a public employer, from the perspective of the principle of non-discrimination on the grounds of religion enshrine in the Council Directive 2000/78/EC of 27 November 2000 (establishing a general framework for equal treatment in employment and occupation). After a look at principles of State neutrality in France, Germany and Belgium, the paper examines this issue by taking a cue from the Conclusions presented by the Advocate General in case C‑148/22. According to the Author, national identity, to which Article 4(2) TEU refers, leaves in this particular sector a wide margin of discretion to the Member States.SOMMARIO: 1. Notazioni introduttive - 2. La rivendicazione del diritto della dipendente comunale belga di indossare il velo islamico e l’oggetto della questione sollevata davanti alla Corte di giustizia - 3. Le peculiarità nelle declinazioni nazionali del principio di “neutralità” dei pubblici dipendenti di Francia, Belgio e Germania. La “neutralità esclusiva” francese - 4. (segue) Il caso emblematico della particolare posizione dei genitori che in Francia accompagnano i figli nelle gite scolastiche - 5. (segue) L’approccio tendenzialmente inclusivo della Germania - 6. (segue) Le incertezze interpretative riguardanti la neutralità belga - 7. La sostanziale “privatizzazione” della controversia operata dall’Avvocato generale - 8. Accezioni “forti” e “deboli” di neutralità del pubblico dipendente e il discutibile profilarsi di un loro diverso impatto sull’identità costituzionale degli Stati membri - 9. Una conclusione provvisoria.